The Manual Graphic Language as a Propaedeutic and Research Tool. The Drawing of Construction Details as a Singular Case Study (diségno, 2025)
In this paper, we present a study on the value and relevance of mastering manual graphic language as an essential tool for the development of educational and research processes, especially in contexts related to the performance of technical and creative skills at advanced levels of critical thinking.In contemporary times, where digital resources have reached a notable level of sophistication, manual drawing continues to hold a significant place due to, among other characteristics, its expressive immediacy in fostering perception, participation, spatial understanding, and creativity.The design of construction details, as a singular case study, demonstrates that technical drawing remains an irreplaceable universal platform for professions with technical and creative roots. Therefore, the propaedeutic training of architects, engineers, and designers is more necessary today than ever.The preview capabilities provided by digital tools, including BIM, are fundamental for contemporary professional practice. However, learning to build and manufacture requires rigorous prior training. Drawing, as a scenario where errors are reversible, allows one to anticipate problems that may arise during the execution phases.
Keywords: graphic language; propaedeutic; research; construction detail; creativity